Registro más austral del tiburón de arrecife de punta blanca Triaenodon obesus (Carcharhiniformes, Carcharhinidae) en el Pacífico Tropical Oriental - Ramírez Segura, Beder (2025)
This study reports the occurrence of Triaenodon obesus (Rüppell, 1837) based on morphological characteristics and DNA sequence analyses of the COI and 16S rRNA genes. In August 2024, a 132 cm total length specimen was captured by spearfishing at Punta Mero, Tumbes (northern Peru). The specimen exhibited a short, rounded snout; the first dorsal fin positioned closer to the pelvic than to the pectoral fins; and distinct white tips on the first and second dorsal fins. DNA sequence analyses of the COI and 16S rRNA genes revealed a high degree of similarity (>99.0%) with T. obesus sequences available in the BOLD and GenBank databases, whereas similarity with other shark species was lower than 96.3% and 98.0%, respectively. This finding increases the known shark diversity in Peruvian waters and extends the southern distribution range of T. obesus in the Tropical Eastern Pacific to Tumbes, northern Peru.